Age-related declines in α-Klotho drive progenitor cell mitochondrial dysfunction and impaired muscle regeneration. Issue 1 (December 2018) - Sahu, A.; Mamiya, H.; Shinde, S.; Cheikhi, A.; Winter, L.; Vo, N.; Stolz, D.; Roginskaya, V.; Tang, W.; St. Croix, C.; Sanders, L.; Franti, M.; et al.
Abstract While young muscle is capable of restoring the original architecture of damaged myofibers, aged muscle displays a markedly reduced regeneration. We show that expression of the "anti-aging" protein, α-Klotho, is up-regulated within young injured muscle as a result of transientKlotho promoter demethylation. However, epigenetic control of theKlotho promoter is lost with aging. Genetic inhibition of α-Klotho in vivo disrupted muscle progenitor cell (MPC) lineage progression and impaired myofiber regeneration, revealing a critical role for α-Klotho in the regenerative cascade. Genetic silencing ofKlotho in young MPCs drove mitochondrial DNA (mtDNA) damage and decreased cellular bioenergetics. Conversely, supplementation with α-Klotho restored mtDNA integrity and bioenergetics of aged MPCs to youthful levels in vitro and enhanced functional regeneration of aged muscle in vivo in a temporally-dependent manner. These studies identify a role for α-Klotho in the regulation of MPC mitochondrial function and implicate α-Klotho declines as a driver of impaired muscle regeneration with age. While young muscle faithfully regenerates damaged myofibers, aged muscle is impaired. Here the authors show the "anti-aging" protein α-Klotho is upregulated in young muscle after damage via promoter demethylation and this regulation is lost in aging, resulting in mitochondrial damage and an impaired healing response.